2019
DOI: 10.1136/bmjopen-2019-033728
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer drug prices and clinical outcomes: a cross-sectional study in Italy

Abstract: ObjectiveTo investigate whether the prices of new anticancer drugs correlated with their relative benefit despite negotiation.DesignRetrospective cross-sectional study correlating new anticancer drugs prices with clinical outcomes.SettingWe did a retrospective cross-sectional study including all new anticancer drugs approved by the European Medicines Agency (EMA) (2010–2016) and reimbursed in Italy.Main outcome(s) and measure(s)Information on clinical outcomes—in terms of median overall survival (OS), median p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
(37 reference statements)
1
16
2
1
Order By: Relevance
“…Likewise, oncology drugs do not show a quicker TTR compared to non-oncology drugs, but actually the TTR for oncology drugs is 2 months longer. It would be interesting to analyse their clinical data in order to assess their therapeutic added value compared to the standard of care at the time of their launch in terms of survival (improved rate or prolongation of survival) to determine whether this had an impact on the TTR (15).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, oncology drugs do not show a quicker TTR compared to non-oncology drugs, but actually the TTR for oncology drugs is 2 months longer. It would be interesting to analyse their clinical data in order to assess their therapeutic added value compared to the standard of care at the time of their launch in terms of survival (improved rate or prolongation of survival) to determine whether this had an impact on the TTR (15).…”
Section: Resultsmentioning
confidence: 99%
“…Italy negotiates drug prices only for binary decisions of approval or non-approval, not considering, during negotiations, whether there is a clear correlation between prices and benefits. Trotta et al ( 39 ) evaluated whether there were better correlations between cancer drug prices and clinical outcomes in a setting where central price negotiations are mandatory for every new medicine. The study demonstrated that:…”
Section: Resultsmentioning
confidence: 99%
“…Итальянские эксперты, проанализировавшие 30 новых противоопухолевых ЛС (зарегистрированы по 35 показаниям), одобренных в Евросоюзе в 2010-2016 гг., и стоимость которых возмещается в Италии, также пришли к заключению, что цены на эти препараты не отражают их терапевтическую пользу [33]. Аналогичное заключение было сделано и в недавно опубликованном анализе ЛС, зарегистрированных в США для лечения злокачественных новообразований ЖКТ [34].…”
Section: соотношение стоимости и терапевтической пользы инновационныхunclassified